Determination of Financial Distress and Stock Prices: The Effect of Financial Performance and Sales Growth (Financial Management Review Literature) - Elviana, Elviana; Hapzi Ali (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews Stock Price Determination and Financial Distress: Financial Performance Analysis and Sales Growth, A Study of Financial Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this research library are that: 1) Financial Performance has an effect on Financial Distress; 2) Sales Growth has an effect on Financial Distress; 3) Financial Performance has an effect on Stock Price; 4) Sales Growth has an effect on Stock Price; and 5) Financial Distress has an effect on stock prices.